2018
DOI: 10.1007/s10637-018-0631-8
|View full text |Cite
|
Sign up to set email alerts
|

Oral Metronomic Vinorelbine (OMV) in elderly or pretreated patients with advanced non small cell lung cancer: outcome and pharmacokinetics in the real world

Abstract: Background Oral metronomic therapy (OMV) is particularly suitable for palliative care, and schedules adapted for unfit patients are advisable. This study investigated the effects of oral vinorelbine given every other day without interruption and its pharmacokinetic profile in patients with advanced lung cancer. Materials and Methods Ninety-two patients received OMV at doses of 20, 30 or 50 mg. Toxic events, clinical benefit and overall survival were analysed. Blood pharmacokinetics were evaluated in 82 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…MTDs were reached at an oral dose of 60 mg 3 times/week for vinorelbine and 85 mg/m 2 for DDP and ORR was 20.8%. This metronomic strategy was tolerable and effective in patients with NSCLC (21).…”
Section: Clinical Trials Of Mctmentioning
confidence: 90%
See 2 more Smart Citations
“…MTDs were reached at an oral dose of 60 mg 3 times/week for vinorelbine and 85 mg/m 2 for DDP and ORR was 20.8%. This metronomic strategy was tolerable and effective in patients with NSCLC (21).…”
Section: Clinical Trials Of Mctmentioning
confidence: 90%
“…Later line treatment. Oral metronomic vinorelbine produced non-negligible survival in elderly or pretreated patients and exhibited stable long-term blood concentrations (21,26,27). Daily oral vinorelbine (30 mg/day) for 21 days with an interruption in treatment for 1 week was well tolerated without dose-limiting toxicity (26).…”
Section: Clinical Trials Of Mctmentioning
confidence: 99%
See 1 more Smart Citation
“…Median PFS was 3.9 months (range 1–13 months) and median OS reached 8.1 months (range 4.0–24.0+ months) with a 12-month survival rate of 22% ( Figure 1 ). These findings are not surprising as other studies failed to identify correlations between patient outcomes and metronomic oral VNR pharmacokinetics [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 70%
“…We know from the literature that mathematical modelling may allow physicians to choose the treatment's regimen which encompasses the timing of administration, based on the evaluation of tolerability and pharmacokinetics [ 31 ]. Recent new trials reported that pharmacokinetics of the aforementioned vinorelbine is stable and the toxicity is associated with high dose of the drug [ 32 ]. Another recent prospective trial explored the activity and feasibility of mVNR 30 mg x 3/wk in selected groups of elderly patients, with advanced disease and poor prognosis owing to the presence of distant metastases and comorbidities.…”
Section: Discussionmentioning
confidence: 99%